Gallbladder disease: a review of cholecystectomy specimens in South Africa - Khan, Zafar Ahmed (My University, 2018)
Background Studies suggest that the rate gallstone disease in Africa is low. Our hypothesis is that gallstone disease in Africa has increased due to urbanization and its associated increases in body mass index (BMI). Methods An audit of cholecystectomies done in South Africa by reviewing gallbladder specimens processed by the South African National Health Laboratory Service (NHLS) from 2004 and 2014 was done. The NHLS services 82.5% of SA's population. Descriptive analysis was performed with comparison done. Urbanization ratios were obtained from Statistics South Africa and BMI data from previously published studies. Results 33467 cholecystectomy specimens were analysed. There was a 92% absolute increase in cholecystectomies during the study period (Pearson r 0.94; p < 0.01) with the overall cholecystectomy rate increasing by 65% from 8·36 to 13·81 per 100000 population. 85% of cholecystectomies were in females, who were significantly younger than males. The data was divided into two equal time periods and compared. During period 2 there was 28·8% increase in cholecystectomies and patients were significantly younger (46·9 vs 48·2 years; p = < 0.0001). The Northern Cape was the only province to show a decline in the cholecystectomy rate in period 2 and was also the only province to record a decline in urbanization ratios. Population based studies in SA have demonstrated a clear association between urbanization and increases in BMI. Interpretation This nationwide African study demonstrates a significant increase in cholecystectomies for younger patients with gallstone disease. A positive relationship between urbanization and cholecystectomy rates has been demonstrated. As urbanization is associated with increases in BMI, this risk factor may be a significant factor in the aetiology of gallstone disease in an apparently low risk population.
A research report submitted to the Department of Surgery, School of Medicine, Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Medicine. Johannesburg, 2018